2021
DOI: 10.3389/fenvs.2021.713562
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Impacts of Human Capital on Green Total Factor Productivity: Regional Diversity Perspective

Abstract: That human capital improves the efficiency of Green Total Factor Productivity has been established in research fields, but the heterogeneous effects of human capital on GTFP and its sustainable mechanisms are unclear. This study examines the effects of human capital accumulation, fiscal spending on education, and innovation on GTFP efficiency under spatial and temporal diversity. Employing panel data from 30 provinces from 2001 to 2018 in China, we analyzed the dynamic and static efficiency of GTFP in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
(28 reference statements)
0
15
1
Order By: Relevance
“…The profit-seeking nature of capital makes the industry focus on the return on investment measured in currency, while ignoring the governance of externalities such as environmental pollution [ 85 , 86 ]. As the industrial upgrading reaches a certain level, the industry gradually transforms from a low value-added, extensive, low-tech one to a high value-added, intensive, and high-tech one [ 87 , 88 ]. Meanwhile, with the implementation of a series of high-quality development strategies, innovation-driven, green development, and other initiatives drive the industrial upgrading process and the green development to run simultaneously, which actively promotes the GEE [ 89 , 90 , 91 ].…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…The profit-seeking nature of capital makes the industry focus on the return on investment measured in currency, while ignoring the governance of externalities such as environmental pollution [ 85 , 86 ]. As the industrial upgrading reaches a certain level, the industry gradually transforms from a low value-added, extensive, low-tech one to a high value-added, intensive, and high-tech one [ 87 , 88 ]. Meanwhile, with the implementation of a series of high-quality development strategies, innovation-driven, green development, and other initiatives drive the industrial upgrading process and the green development to run simultaneously, which actively promotes the GEE [ 89 , 90 , 91 ].…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…One of the most important indicators is green total factor productivity (GTFP), which brings ecological and environmental factors into the assessment criteria of economic development quality and pursues the harmonious coexistence of economic growth and resources and the environment. For example, Xiao and You (2021) used the three-stage data envelopment analysis (DEA) method to calculate the green total factor productivity of 30 provinces in China and found that there were significant regional differences in China's green total factor productivity. Feng et al (2021) also paid attention to the importance of environmental quality to the level of economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, scientific and technological progress is the core driving force for the transformation of the modes of marine economic development, which helps to improve the quality of marine economic development. Human capital can promote scientific and technological progress through research and development (R&D); create new market demand; and improve the investment, demand, and consumption structures, which then accelerates the optimization and upgrade of industrial structures, brings high-quality and effective supply and promotes the improvement of GTFP [ 48 ].…”
Section: The Mechanisms Of Influencing Factors On the Gtfp ...mentioning
confidence: 99%